2016
DOI: 10.1177/0954405416673113
|View full text |Cite
|
Sign up to set email alerts
|

Grinding of flat glass with Fe- and Cu-based diamond tools

Abstract: Preparation of grinding wheels is the most important effective factor in glass machining. This article presents the comparison of the iron-and copper-based grinding tools. The performance of the tools is investigated based on technical and commercial aspects using same cutting speeds, feeds, and sizes of diamond grits. Scanning electron microscope is used in order to observe the microstructures of cutting tools. The service life of the grinding tools is determined on the production line in a flat glass plant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…However, the solid drill has a large amount of material removal during hole processing, which generates a large axial force, so some scholars proposed the ''grinding instead of drilling'' method, using a hollow-type trepanning bit to drill holes in the form of grinding. Ozturk S 19 studied the hole processing of CFRP using an electroplated diamond trepanning bit and found that the trepanning bit could obtain a large critical axial force, which was beneficial to reducing the generation of delamination defects. According to the research above, a tool's structure and material will have an impact on how well a workpiece is machined, and a well-designed tool will significantly enhance the quality of the hole.…”
Section: Introductionmentioning
confidence: 99%
“…However, the solid drill has a large amount of material removal during hole processing, which generates a large axial force, so some scholars proposed the ''grinding instead of drilling'' method, using a hollow-type trepanning bit to drill holes in the form of grinding. Ozturk S 19 studied the hole processing of CFRP using an electroplated diamond trepanning bit and found that the trepanning bit could obtain a large critical axial force, which was beneficial to reducing the generation of delamination defects. According to the research above, a tool's structure and material will have an impact on how well a workpiece is machined, and a well-designed tool will significantly enhance the quality of the hole.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of soda-lime glass, which is an organic material in many engineering fields, is superior in comparison to other materials with hardness, low density, low heat and electrical conductivity [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%